Dr. Khairul Anuar produces CLINKROOF, sustainable green roof system based on palm oil waste - Nur Hartini, Mohd Hatta (2023)
PEKAN, 27 December 2022 - Flash floods and rising temperatures in big cities due to urban heat islands reported by the mass media are happening more and more often lately.